1996
DOI: 10.1002/etc.5620150206
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hydroxyl radical (·OH) in illuminated surface waters contaminated with acidic mine drainage

Abstract: Abstract-Formation rates and steady-state concentrations of hydroxyl radical (• OH) in illuminated surface water samples collected in west-central Indiana that receive acidic mine drainage runoff are reported. Formation rates for• OH in samples were measured by the addition of 1 ϫ 10 Ϫ3 M benzene prior to illumination in order to effectively scavenge all of the • OH formed, thereby yielding phenol. The• OH formation rates were calculated from the measured phenol formation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…• OH photogeneration has been previously observed in acidic mine drainage water (Allen et al, 1996).…”
Section: Discussionmentioning
confidence: 76%
“…• OH photogeneration has been previously observed in acidic mine drainage water (Allen et al, 1996).…”
Section: Discussionmentioning
confidence: 76%
“…Still, the mechanisms underlying • OH formation from non- 3 DOM* species (e.g., excited state oxidants of unknown identity) warrant further investigation. Other pathways of • OH formation, such as photo-Fenton reactions and NO 3 – photolysis, ,, might be operative apart from direct photolysis of DOM. ,,,, Compared to naturally acidic waters containing elevated [Fe] (e.g., acid mine drainage waters, , coastal rivers, , Arctic streams), Adirondack lake waters featured much lower [Fe] (0.73 ± 1.02 μM) and mildly acidic pH, so the photo-Fenton pathway was less likely a main contributor to Φ app, • OH despite the fact that • OH formation does not necessarily scale proportionally to [Fe] , and could operate at circumneutral pH. ,, On the other hand, the low [NO 3 – ] to [DOC] ratio (0.13 ± 0.17 mg NO 3 – /mg C) in Adirondack lake waters indicated that the contribution of NO 3 – photolysis to Φ app, • OH was minor as this pathway only becomes a competitive source of • OH in surface waters with elevated [NO 3 – ] (e.g., ≥ 2.0 mg NO 3 – /mg C). ,, …”
Section: Results and Discussionmentioning
confidence: 99%
“…Reactive oxygen species ͑ROS͒, which include hydrogen peroxide ͑H 2 O 2 ͒ and hydroxyl radicals ͑ · OH͒ occur in rain 1,2 and surface waters. 3,4 ROS play an important role in natural processes in aquatic systems, including, radiolysis, 5,6 pyrite oxidation, [7][8][9] and photochemical oxidation. 10,11 Hydrogen peroxide also is intentionally added to wastewaters to promote in situ oxidation processes 12,13 by leveraging the extreme reactivity of radicals toward organic pollutants.…”
Section: Introductionmentioning
confidence: 99%